2017
DOI: 10.1097/bot.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Safely Reduced Blood Loss in Hemi- and Total Hip Arthroplasty for Acute Femoral Neck Fracture: A Randomized Clinical Trial

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 33 publications
4
65
0
4
Order By: Relevance
“…The search yielded 235 unique results. Following full-text screening, 10 studies were deemed appropriate for inclusion in this study [13][14][15][16][17][18][19][20][21][22] (refer Figure 1). All trials had a predetermined transfusion protocol and these also differed ( Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The search yielded 235 unique results. Following full-text screening, 10 studies were deemed appropriate for inclusion in this study [13][14][15][16][17][18][19][20][21][22] (refer Figure 1). All trials had a predetermined transfusion protocol and these also differed ( Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…After full texts carefully read for eligibility, two studies were excluded, because they were just an abstract. 16 , 17 Finally, 12 RCTs 18 – 21 , 23 – 30 and 1 retrospective cohort study 22 were included. The characteristics of all included studies are shown in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The value of weighted kappa for the agreement on these studies between reviewers was excellent ( κ = 0.72). Ten studies 18 – 21 , 23 , 25 , 26 , 28 – 30 were of high quality, and two studies were of moderate quality. 24 , 27 The randomization methods were explicitly introduced in nine studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent 10 years, surgical techniques and perioperative management guidelines have made gratifying progress in THA, promoting the rapid recovery of patients. Tranexamic acid (TXA), a synthetic analog of lysine, inhibits fibrinolysis by competitively blocking the lysine binding site of plasminogen, often used for joint replacement to reduce perioperative blood loss, and it has anti‐inflammatory effects. Dexamethasone (DEX), with a strong anti‐inflammatory agent, has been widely used to reduce inflammatory markers, prevent PONV, and relieve postoperative pain and fatigue in various perioperative periods.…”
Section: Introductionmentioning
confidence: 99%